2018
DOI: 10.1017/s002185961700096x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in plasma constituents, growth and egg production traits due to selection in three genotypes of Japanese quail

Abstract: The present investigation was carried out to estimate the effects of genotype and sex on growth and laying performance and assess the variations in plasma constituents in the tested genotypes and their relations with productive traits after four generations of selection. Data of growth and laying performance on 1440 females and males of Japanese quail were taken from the three quail genotypes: maternal (MG), long shank length (LSG28) and control (CG) genotypes. Genotype significantly affected all studied growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…The selected line attained AFE at earlier age with heavier BWAFE and lower DN10 and AGE10 than the control line whereas, the control line had insignificantly heavier AEWFM than selected line (Table 2). Similarly, line had significant effect on AFE as reported by Farrag (2011), Narendra Nath et al (2011, Sadeghi et al (2013), Mahmoud et al (2014), Emam (2015), Meabed (2015) and Farahat et al (2018). However, Karabağ et al (2010) and Alkan et al (2013) reported insignificant line effect on AFE.…”
Section: Results and Discussion Performance Of Egg Production-relatedmentioning
confidence: 62%
See 2 more Smart Citations
“…The selected line attained AFE at earlier age with heavier BWAFE and lower DN10 and AGE10 than the control line whereas, the control line had insignificantly heavier AEWFM than selected line (Table 2). Similarly, line had significant effect on AFE as reported by Farrag (2011), Narendra Nath et al (2011, Sadeghi et al (2013), Mahmoud et al (2014), Emam (2015), Meabed (2015) and Farahat et al (2018). However, Karabağ et al (2010) and Alkan et al (2013) reported insignificant line effect on AFE.…”
Section: Results and Discussion Performance Of Egg Production-relatedmentioning
confidence: 62%
“…Emam (2015) reported that selection for high BW21 resulted in desirable decrease in DN10 of -11.71 days for the selected line fed 24% CP diet quails vs. 13.28 days for the control fed 24% CP diet quails. There were significant differences among lines for DN10 favoring the selected line for selection index (AFE, BWAFE and DN10) and trends of selection changes were towards early maturity and shorter DN10 (Mahmoud et al, 2014and Farahat et al, 2018. Regardless of generation number, averages for AEW were higher in selected lines for high body weight than those in the control lines (Karabağ et al, 2010, Farrag, 2011and Narendra Nath et al, 2011.…”
Section: Results and Discussion Performance Of Egg Production-relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable improvement in the productivity of many poultry species is due to selection programs that focused on rapid growth with not neglecting environmental factors such as feeding and housing systems (Ahmed, 2012). Many studies have evaluated the genetics of growth performance of different poultry species estimating the genetic parameters of the growth traits as in chicken (Radwan et al, 2018 andBerger et al, 2022), quail (Farahat et al, 2018and Sarvari-Kalouti et al, 2023), and ducks (Cyriac et al, 2020and El-Deghadi et al, 2022. However, the available information on pigeon productivity is very scarce as pigeons did not receive the required attention through genetic improvement systems, as well as from the side of care and nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic selection is a powerful method for genetic improvement of quail performance. It could alter some physiological relationships and metabolic processes either in growth (Farahat et al ., 2018) or egg production traits (Abou Khadiga et al ., 2017). Growth pattern varies among individuals due to genetic background (Narinç et al ., 2010 b ) and sex (Ojedapo and Amao, 2014).…”
Section: Introductionmentioning
confidence: 99%